Physical characteristics of puddle rice soils as influenced by agro-ecological and land situations - SAIKIA, MRIDUPAWAN; BHATTACHARYYA, D.; PATGIRI, D. K.; THAKURIA, R. K.; DEKA, P.; BORAH, NILAY (Journal of Soil and Water Conservation, 2020)
A study was carried out to evaluate the long-term impact of rice (transplanted) sole crop on physical properties of soils under different agro-ecological and land situations of Jorhat district, Assam. Soil samples were collected from Titabor, representing Humid Alluvial Flood Free (HAFF), Baghchung, representing Humid Alluvial Flood Prone (HAFP) and Nimatighat, representing sandbar, locally known as Charland (CL) situations of the district. Representative samples were collected from three soil depths viz. 0-15, 15-30 and 30-45cm under each of lowland and medium land situations at every agro-ecological situation (AES). Soil samples were analyzed for pH, organic carbon (OC), texture, bulk density (BD), particle density (PD), porosity, maximum water holding capacity (MWHC), volume expansion(VE), saturated hydraulic conductivity (KS), infiltration rate, water stable aggregates and mean weight diameter (MWD). The pH, OC, BD and PD values ranged from 4.43 to 6.49, 7.0 to 19.4 g/kg, 1.31 to 1.40 Mg/m3 and 2.35 to 2.56 Mg/m3, respectively. The porosity, MWHC and VE values ranged from 36.5 to 41.6 %, 31.3 to 43.3 % and 7.13 to 9.52 m3/m3, respectively. Hydraulic properties such as KS and infiltration varied from 1.45 to 6.80 mm/h and 7.19 to 16.97 mm/h, respectively. MWD values ranged from 0.55 to 2.83 mm within 0- to 45 cm depth in all the ecological situations. The correlation of KS was positive with sand (0.478**) and negative with clay (-0.630**) content of soils, while MWD showed positive correlation with clay (0.541**) and OC and showed negative correlation with BD (-0.808**), all being statistically significant at 1% probability level.